A 28 GHz CMOS Butler matrix for 5G mm‐wave beamforming systems. Issue 7 (10th March 2020) - Park, Jeongsoo; Kim, Jeong‐Geun
Abstract: This paper presents 28 GHz CMOS 8×8 Butler matrix which can improve the beamforming capability in 5G mm‐wave communication systems. The proposed 28 GHz N×N Butler matrix can increase the number of the antenna beam pattern from N to 2N − 1 beams with DP8T switch network including a lumped 180° coupler, 22.5° phase shifter, and switches. The beamformer is fabricated using 65 nm CMOS process and the size is 1.8 × 2.5 mm 2 . The DC current consumption is 145 mA (Rx) and 180 mA (Tx) at 2.5 V supply voltage. The proposed 28 GHz CMOS 8×8 Butler Matrix is able to make 15 beam patterns with ±63° beam scan and low sidelobe level, which is suitable in low cost 5G mm‐wave beamforming system.